Problems Associated with the Public Procurement Process with Special Focus on public Building Construction Projects of Dhulikhel municipality, Kavreplanchowk District, Nepal - Mehata, Yogendra Prasad; Dahal, Khetraj; Gyawali, Prakash (International Journal on Engineering Technology, 2026)
This study investigates challenges in public procurement processes, focusing on public building construction projects in Dhulikhel Municipality, Kavrepalanchowk District, Bagmati Province, Nepal. The research aimed to identify operational and administrative issues affecting procurement implementation at the municipal level. A mixed-method approach was adopted, combining qualitative and quantitative data collected through structured questionnaires, field observations, in-depth interviews, and focus group discussions. Findings indicate that procurement in Dhulikhel Municipality faces multiple challenges, including staff absenteeism, inadequate compliance with procurement laws, and limited use of the electronic government procurement (e-GP) system due to low ICT capacity. These issues have led to inefficiencies and delays, negatively impacting project performance and the quality of public construction works. To address these challenges, the study recommends enhancing institutional accountability, expanding digital procurement adoption, promoting ethical practices, and strengthening monitoring and evaluation mechanisms. Additionally, capacity building and clear procedural guidelines are emphasized to ensure fair, efficient, and transparent procurement operations. The insights from this research are intended to support local authorities, policymakers, and practitioners in improving procurement management and governance, ultimately contributing to more effective public infrastructure development.